Political Budget Cycle and Financial Losses: An Indonesian Case - Ermanda Mulki Ghaniyar; Riatu Mariatul Qibthiyyah (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2021)
This study aims to test the Political Budget Cycle (PBC) in Indonesia as one of the world's largest democracies, specifically testing the presence of PBC across types of local government expenditures. This study further analyzed the effect of changes in expenditure composition during election years on financial local government losses. The financial losses are defined as irregularities in regional finance management found in the Audit Board of The Republic of Indonesia (BPK) audit report. This study uses the data at the district and city levels (local expenditures and financial losses) from 2014 to 2019 and adopts a fixed-effect panel data specification. The empirical estimations show the following evidence: (1) PBC phenomenon occurs in Indonesia, especially on government grants (belanja hibah), expenditure on goods and services, and capital expenditures; (2) There was no difference in PBC behavior between a region having an incumbent running for re-election and a region with incumbents from the previous election; (3) The existence of PBC tend to increase local government (financial) losses.